After the New Perspective: Works, Justification and Boasting in Early Judaism and Romans 1-5 - Gathercole, Simon J. 1974- (2001)
A dissertation exploring how ‘boasting’ functions in Romans 1–5; this question cuts to the heart of the debates about the ‘New Perspective’ on Paul’s relation to his Jewish contemporaries.
Keywords: Boasting; Justification; new perspective on paul; paul; New Testament